The rhetorical complexity of competitive and common victimhood in conversational discourse. (7th June 2017) - McNeill, Andrew; Pehrson, Samuel; Stevenson, Clifford
Abstract: Much current research on collective victimhood acknowledges the role of rhetoric but does not fully address the implications for micro‐level variation in personal expressions of victimhood. The focus has tended to be on individual differences in collective victimhood construals where people may either see their group as the sole possessor of victim status or may incorporate other groups into an inclusive category. Although recent research sees a strategic element in some 'inclusivity', we argue that all claims of victimhood are strategic. By using a discursive approach, we show variability in the expression of victimhood and how this accomplishes different activities in conversations. Several focus groups consisting of victims from Northern Ireland were analysed to identify presentations of victimhood and their relation to the unfolding dynamics of the conversation. We demonstrate that presentation of victimhood is an interactional concern, link this to the concept of 'needs' and suggest implications this might have.